NEOLIBERALISM AND AUTHORITARIAN DRIFT - Ayala Saavedra, Roberto (2022)
The article deals with studying the 'neoliberal' phenomenon, that is, the set of public, economic and social policies aimed at producing not only a change in the model of accumulation and growth, but also at inducing a strong social restructuring, modifying the cultural climate and mindsets. In this framework, it examines the correlated authoritarian drift, as well as the civilizational crisis in which the entire process is inscribed.